Delinkvention: Evolution of the Construct and the Concept - Paulauskas, Rolandas (Special Education, 2025)
The term ‘delinquency’ became widespread in the Lithuanian language only in the 1970s, yet the construct itself is an ancient social phenomenon. Its emergence in Western societies was shaped by social, cultural, and economic transformations. Many scholars agree that several key factors played an important role in forming the delinquency construct: the ‘discovery’ of childhood and adolescence as distinct life stages; the parens patriae doctrine that spread through English legal practice; the reform and child-saving movements in the United States; and, in the latter half of the twentieth century, the rise of positivist research grounded in psychology and criminology. This article provides a detailed analysis of how the concept of childhood evolved across different historical periods, examines the role of the parens patriae doctrine in protecting the interests of all children, and discusses the significance of the reformatory initiatives and the child-saving movement in securing the welfare of minors. It also emphasizes the importance of positivist research in psychology and criminology. The study concludes that the ‘discovery’ of childhood revealed minors to be physically and psychosocially distinct from adults — individuals who lack control over their environment and are inherently vulnerable. For this reason, all children, including those from at-risk groups, require appropriate care, which the parens patriae doctrine sought to guarantee since the Enlightenment. Finally, positivist psychology and criminology have shown that the causes of antisocial behavior are often linked to the psychosocial development of the individual, the immediate social environment, community disorganization, and limited access to opportunities. Consequently, minors should be subject to reduced criminal liability and a lower age of legal responsibility. Research also demonstrates that rehabilitative and educational strategies are far more effective than punitive ones. In conclusion, delinquency should be understood as an evolving and continually transforming construct.